Changes in muscle strength, jump, and sprint performance in young elite basketball players: the impact of combined high-speed resistance training and plyometrics - Yáñez-García, J. M.; Rodríguez-Rosell, D.; Mora-Custodio, R.; González-Badillo, J. J. (The Journal of Strength and Conditioning Research, 2022)
This study aimed to compare the effect of a combined resistance training (RT) and plyometrics on strength, sprint, and jump performance in basketball players of different ages. Thirty three elite basketball players from the same academy were categorized into 3 groups by chronological age: under-13 (U13, n = 11); under-15 (U15, n = 11); and under-17 (U17, n = 11). Players participated in a 6-week strength training program that included 2 sessions each week and consisted of full squats with low loads (45-60% 1 repetition maximum) and low volume (2-3 sets and 4-8 repetitions), jumps, and sprint exercises. All repetitions were performed at maximal intended velocity. In addition to strength training sessions, subjects performed 4 on court basketball training sessions plus 2 official matches per week. After training program, all 3 experimental groups resulted in significant improvements (p < 0.05-0.001) in maximal strength (Delta: 9.2-27.3%; effect size [ES]: 0.38-0.82), countermovement jump height (Delta: 6.6-11.6%; ES: 0.37-0.95), and sprint time in 10 and 20 m (Delta: -3.9 to -0.3%; ES: 0.09-0.69) for all experimental groups. Comparison between groups showed that training program was more effective in inducing improvements in most variables assessed for U13 compared with U15 (ES: 0.11-0.42) and U17 (ES: 0.20-0.43), whereas differences between U15 and U17 were relevant in jump and strength parameters (ES: 0.20-0.35). Therefore, these findings suggest that high-speed RT combined with plyometrics produces increments in several important variables, including strength, jump, and sprint, to yield high performance during a match in young basketball players. However, training program used seems to be generally less effective as the age of the basketball players increased.